2009
DOI: 10.4049/jimmunol.182.3.1509
|View full text |Cite
|
Sign up to set email alerts
|

B and T Lymphocyte Attenuator Regulates B Cell Receptor Signaling by Targeting Syk and BLNK

Abstract: B and T lymphocyte attenuator (BTLA) functions as a negative regulator of T cell activation and proliferation. Although the role of BTLA in regulating T cell responses has been characterized, a thorough investigation into the precise molecular mechanisms involved in BTLA-mediated lymphocyte attenuation and, more specifically, its role in regulating B cell activation has not been presented. In this study, we have begun to elucidate the biochemical mechanisms by which BTLA functions to inhibit B cell activation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 59 publications
6
93
0
Order By: Relevance
“…C TIL after TCR activation and could potentially interact with HVEM, a prosurvival effect mediated through LIGHT is unlikely because it has no obvious signaling motif, 44 and it has been reported that signaling through HVEM upon binding to LIGHT might induce a different T-cell survival via NF-kB activation. 45 It is also possible that cis interaction or a T-T interaction between BTLA and HVEM could mediate survival via HVEM, as shown by Carl Ware's group.…”
Section: Discussionmentioning
confidence: 99%
“…C TIL after TCR activation and could potentially interact with HVEM, a prosurvival effect mediated through LIGHT is unlikely because it has no obvious signaling motif, 44 and it has been reported that signaling through HVEM upon binding to LIGHT might induce a different T-cell survival via NF-kB activation. 45 It is also possible that cis interaction or a T-T interaction between BTLA and HVEM could mediate survival via HVEM, as shown by Carl Ware's group.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, TRAIL could be another potential negative factor contributing to T-cell suppression in HIV infection. BTLA (CD272) inhibits TCR-mediated signaling via its immunoreceptor tyrosine-based inhibitory and switch motifs (18,62). Likewise, CD160 mediates negative signaling and is induced in a similar manner as CTLA-4 in T cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, as previous studies suggest that TNFRSF14 aberrations may confer a poor prognosis in patients treated with chemoimmunotherapy, 4 it is likely that additional or alternative HVEM-mediated mechanisms impact on FL B-cell survival in the autologous setting. As BTLA is also expressed on B cells, and negatively regulates B-lymphocyte transformation and malignant B-cell survival, [35][36][37] reduction of HVEM ligation of BTLA on FL B cells either in cis or trans (from neighboring tumor cells) could potentiate tumor growth and survival in this setting.…”
Section: Discussionmentioning
confidence: 99%